Hepatomegaly and type 1 diabetes: a clinical case of Mauriac's syndrome - Fortunato Lombardo; Stefano Passanisi; Albino Gasbarro; Giovanni Tuccari; Antonio Ieni; Giuseppina Salzano (BMC, 2019)
Abstract Background Hepatic glycogenosis is characterized by excessive glycogen accumulation in hepatocytes and represents a complication of poor controlled type 1 diabetes. It can be caused by excessive insulin doses or recurrent ketoacidosis episodes. Mauriac's syndrome is a rare disease, which includes short stature, growth maturation delay, dyslipidemia, moon facies, protuberant abdomen, hepatomegaly with transaminase elevation. It has become even less common after the emergence of advances on diabetes treatment, but still exists. Recent reports described glycogenosis without the full spectrum of Mauriac's syndrome in both adults and children with brittle diabetes. Clinical, laboratory and histological abnormalities are reversible with appropriate glycemic control. Case presentation We hereby report a case of 11-year-old male who presented with hepatic glycogenosis mimicking Mauriac's syndrome. The patient was admitted at our Pediatric Diabetes Clinic for marked hepatomegaly, short stature and for the poor metabolic control. Blood investigations and liver tests excluded most of major causes of hepatopathy. A liver biopsy allowed us to make diagnosis of hepatic glycogenosis. To control hyperglycaemia, initially we titrated daily insulin dosage, and then intravenous insulin treatment was practiced with the consequent normalization of liver enzymes. Conclusion Mauriac's syndrome should be considered in subjects with brittle type 1 diabetes and hepatomegaly.